Efek ERAS (Enhanced Recovery After Surgery) pada Pasien ORIF dengan Spinal Anastesi: Studi Kasus - Salsabilla, Dhevinda Nadia; Primanda, Yanuar; Suprianto (MES Bogor, 2025)
This study aimed to evaluate the effects of the Enhanced Recovery After Surgery (ERAS) protocol in a Post-Open Reduction Internal Fixation (ORIF) patients with lower extremity fractures. The case study was conducted on two patients: an adult patient with a closed-tibialis dextral fracture and an elderly patient with an intertrochanteric femur sinistral fracture. Data collection methods included direct observation, interviews, and the utilization of ERAS-standardized assessment tools such as the Visual Analog Scale (VAS), Hamilton Anxiety Rating Scale (HARS), and early mobilization observation forms. The results showed a decrease in pain within the first 24 hours post-ORIF from VAS 5 to 2, a progression of early mobilization from sitting to standing within a day, and an anxiety reduction. The discussion emphasizes the key of ERAS components: multimodal pain management, early ambulation, and patient education. The study concluded that ERAS is effective in enhancing both physical and psychological recovery in post-ORIF patients especially to manage pain, improve mobilization and reduce anxiety.